Technical efficiency of potato production in mid western terai region of Nepal - Lamichhane, Jeevan; Acharya, Basistha; Sharma, Tara (Journal of Agriculture and Natural Resources, 2019)
A study was done in 2018 to estimate the technical efficiency of potato production in mid western terai region of Nepal.30 households each from Dang, Banke and Bardiya districts were interviewed. Maximum likelihood estimate of the parameter showed the mean technical efficiency of 0.79 which indicated a high scope of increasing the production with the improvement of production technology. The coefficient for the parameter seed, Urea, DAP, MOP and labour were positive contributing for the production of potato. The parameter Compost, pesticides, herbicides and hour of tractor use were negative. The use of these input could be improved for increasing the production of potato. The farm specific variables Education, contact with the extension agent and farm size showed negative coefficient which causes less inefficiency of the farmers in production of potato while the coefficient for Age was estimated to be positive.